Spills of emulsified fuels : risks and response (Compass series (Washington, D.C.), 2002)
Spills of Emulsified Fuels: Risks and Response is part of an evolving body of work conducted by the National Research Council (NRC) to help inform debate and decision-making regarding the ecological consequences of releases associated with the widespread use of fossil fuels. Like earlier NRC reports, it attempts to understand the chemical, physical, and biological behavior of a complex mix of compounds that make up various petroleum hydrocarbon-based fuels. The specific risk factors presented by emulsified fuels are difficult to characterize, mainly because there have been no spills of emulsified fuels to date, and thus there is little practical experience with these products.